Identification of presenilin mutations that have sufficient gamma-secretase proteolytic activity to mediate Notch signaling but disrupt organelle and neuronal health - Zahra Ashkavand; Kerry C. Ryan; Jocelyn T. Laboy; Ritika Patel; Brian Geller; Kenneth R. Norman (Neurobiology of Disease)
Mutations that cause familial Alzheimer's disease (AD) are predominantly found in the presenilin (PSEN) encoding genes PSEN1 and PSEN2. While the association of PSEN mutations with familial AD have been known for over 20 years, the mechanism underlying the impact these mutations have on disease is not fully understood. PSENs are phylogenetically conserved proteins that are found in diverse multicellular organisms ranging from plants to humans. PSENs form the proteolytic core of gamma-secretase that is required for cleaving type I transmembrane proteins, such as Notch receptors and the amyloid precursor protein. Importantly, familial AD-associated PSEN mutations are broadly distributed and do not clearly define a specific PSEN function essential for neuronal fitness. Here, using C. elegans as a model organism to study the in vivo functions of PSENs, we confirm that C. elegans PSEN plays a pivotal role in gamma-secretase proteolytic activity as well as maintaining neuronal and organelle health. Notably, we demonstrate that these two functions can be genetically uncoupled. Our research identifies several conserved familial AD-like missense mutations in the endogenous sel-12 gene, which encodes C. elegans PSEN. These mutations preserve sufficient gamma-secretase proteolytic activity to mediate Notch signaling but abolish PSEN's role in supporting neuronal and organelle health. Furthermore, we provide evidence that these familial AD-like missense mutations disrupt mitochondrial calcium regulation, ultimately leading to neuronal dysfunction. These results indicate that C. elegans PSEN plays at least two independent roles: one that mediates gamma-secretase proteolytic activity and another that mediates organelle and neuronal health.